We can rewrite this function using this rule for quadratics:
color(red)(x)^2 - color(blue)(y)^2 = (color(red)(x) + color(blue)(y))(color(red)(x) - color(blue)(y))x2−y2=(x+y)(x−y)
f(x) = -3x^4(color(red)(x)^2 - color(blue)(9))f(x)=−3x4(x2−9)
f(x) = -3x^4(color(red)(x)^2 - color(blue)(3)^2)f(x)=−3x4(x2−32)
f(x) = -3x^4(color(red)(x) + color(blue)(3))(color(red)(x) - color(blue)(3))f(x)=−3x4(x+3)(x−3)
Now, we can solve each term on the left side of the function for 00 to find each zero of the function:
Solution 1:
-3x^4 = 0−3x4=0
(-3x^4)/color(red)(-3) = 0/color(red)(-3)−3x4−3=0−3
(color(red)(cancel(color(black)(-3)))x^4)/cancel(color(red)(-3)) = 0
x^4 = 0
root(4)(x^4) = root(4)(0)
x = 0
Solution 2:
x + 3 = 0
x + 3 - color(red)(3) = 0 - color(red)(3)
x + 0 = -3
x = -3
x = 0
Solution 3:
x - 3 = 0
x - 3 + color(red)(3) = 0 + color(red)(3)
x - 0 = 3
x = 3
The Solutions Are: x = {-3, 0, 3}
The graph of the function touch the x-axis at 0:
graph{y + 3x^6 - 27x^4 = 0 [-10, 10, -50, 400]}